Contemporary Realities in Nigerian Spoken Word Poetry - Omajuwa , Ogugua; Onovwiona , Solomon (International Journal of Arts, Languages, Linguistics and Literary Studies, 2022)
Poetry uses words to recreate imaginative, emotional or intellectual experience of the poet in such a way that it arouses similar experience in the mind of its listener or reader. African poetry, in addition to this, is a poetry characterised by its immense dedication to the promotion of its people’s heritage and its profound ability at imagining their realities. In this regard, Nigerian spoken word poetry is nothing but a full-fledged subgenre of African poetry just like its page counterpart. Spoken word poetry is poetry that is written but meant for the stage. This poetry is fully actualized only when it is performed. This paper investigates selected spoken word poems by award winning Nigerian spoken word poets: Efe Paul Azino, Dike Chukwumerije, Wana Udobang, and Titilope Sonuga. The themes of the poems will be the focus of the study. The paper concludes that Nigerian spoken word poetry is a subgenre of Nigerian poetry, as it explores contemporary realities and shares the same vision with its page counterpart, to unite Nigerians and make Nigeria a better place.